A STUDY OF DIGITAL BUSINESS IN INDIA AND ITS IMPACT ON GROWTH IN INDIAN ECONOMY. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Indian Economy is one of the fastest growing economies in the world and it also strengthening its roots in digitalization.Starting with the traditional economy the India is now approaching towards economy worth the Giant “$1 Trillion”.According to Ravi Shankar Prasad (Mo IT). Further he extended his saying to its Contribution of Digital economywould be $200 Billion by 2020 in overall economy of India. Economy refers to the state of a country or region in termsof the production and consumption of goods and services and the supply ofmoney.Talking about the Digital Business it explains Digital businesses use technology to create new value in business models,customer experiences and the internal capabilities that support its core operations and as a part of digital economy theDigital Business is playing a role of driving factor of Indian Economy. The major increase in digital business took placein this decade while last 5 Years found to be the Pioneer of the economy. The motive of ` NDA government and theirdecision of Digital India gave a sudden rise to the Digital Business Sector in India Digital Index went up to 56% after2015. In 2017-18 it was found that the digital Economy has given a contribution of 8% in total GDP of the country.The major findings tell that Digital India Movement and demonetization that occurred in November 2016 and theinitiative of Going Cashless also increased the Digital Business as it was the major event in Digital economy of theCountry.In this research, we have studied an impact of Digital Business in Indian Economy and its future scope and challengesin growing an economy of ournation.